INDEKS KEANEKARAGAMAN JENIS SERANGGA PADA PERTANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) DI KEBUN HELVETIA PT. PERKEBUNAN NUSANTARA II - Gevit R Tambunan; Mena Uly Tarigan; Lisnawita Lisnawita (Jurnal Agroekoteknologi, 2013)
Insect Species Diversity Index in Oil Palm (Elaeis guineensis Jacq.) Planting in Helvetia Estate, PT.Perkebunan Nusantara II. The purpose of this study was to find out the insect species diversity index inoil palm (Elaeis guineensis Jacq.) planting in Helvetia Estate, PT. Perkebunan Nusantara II. This surveystudy was conducted from June to August 2101 in Helvetia Estate, PT. Perkebunan Nusantara II, DeliSerdang District with the altitude of ± 23 meters above sea level. The insects were caught by busingsweep net, pit fall trap, and light trap, then they were observed at the Plant Pest and Disease Laboratory,Faculty of Agriculture, University of Sumatera Utara. The result of this study showed that 298 insectsconsisting of 9 orders and 29 families were trapped and caught in the oil palm plantation area which hasproduced and 367 insects consisting of 10 orders and 34 families were trapped and caught in the oil palmplantation area which has not produced.The value of Insect Species Diversity Index according to thehighest Shanon-Weiner (H’) in the oil palm plantation area which has produced is 2.9276 (adequate) andin the oil palm plantation area which has not produced is 2.9848 (adequate). While the value ofSorensen’s Quotien of Similarity for the kinds of insects in both areas is 79.365%.Keywords: Diversity index, oil palm, insect